2012
DOI: 10.1111/j.1365-2133.2012.11082.x
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy, sunscreen and sunbed use: an uneasy association

Abstract: SummaryBackground Skin cancer can largely be prevented by avoiding unsafe ultraviolet radiation (UVR) exposure. The evidence on potential drivers of sunscreen and sunbed use is extensive, yet in some cases, such as education, remains rather unclear. Health literacy is receiving increasing attention, but its effect on tanning decisions has not yet been explored. Objectives To explore the association between health literacy and tanning behaviour, in terms of sunscreen and sunbed use. Methods Self-reported data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
(44 reference statements)
2
20
2
1
Order By: Relevance
“…Even so, we were able to detect alarmingly high prevalence rates in several European countries. Our analysis of the trend between prevalence and latitude confirmed the existence of a North‐South gradient of sunbed use in Europe, with northern countries more likely to use sunbeds, as previously reported . Nonetheless, we found interesting exceptions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Even so, we were able to detect alarmingly high prevalence rates in several European countries. Our analysis of the trend between prevalence and latitude confirmed the existence of a North‐South gradient of sunbed use in Europe, with northern countries more likely to use sunbeds, as previously reported . Nonetheless, we found interesting exceptions.…”
Section: Discussionsupporting
confidence: 90%
“…Although sunbed use has been widely associated with high educational level, we were able to confirm this association only partly. Indeed, our multivariate analysis excluded a large effect of educational attainment on sunbed use.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Women have consistently been reported to be the most eager sunbed users in Europe . Interestingly, most studies have reported that females are two to three times more likely to use indoor tanning than males . Women have also been reported to do more sessions and to spend a longer cumulative time under the lamps .…”
Section: Who Uses Sunbeds In Europementioning
confidence: 99%
“…U dva obrađena rada analizirana su tri pitanja, za koje je zaključeno da su efikasna u otkrivanju neefikasne ili marginalne zdravstvene pismenosti među odraslom populacijom pacijenata [10,13]. Ova tri pitanja su nastala i procenjena na osnovu njihove efikasnosti u identifikaciji pacijenata sa neefikasnom ili marginalnom zdravstvenom pismenošću upoređenom sa S-TOFHLA (kratka verzija, engl.…”
Section: Wwwtmgorgrsunclassified